Exploring HIV and STI prevalence, sexual practices and drug use among self-identified women who have sex with women in Blantyre, Malawi - Botha, Winnie Agnes (Kamuzu University of Health Sciences, 2022)
Women who have sex with women (WSW) are mostly not included in Human Immunodeficiency Virus (HIV) and Sexually Transmitted Infections (STI) prevention interventions since female-female sex is presumed to be low risk. However, studies from other countries have reported significant STI burden in WSW. No study has been done in Malawi. To explore HIV, STI prevalence, drug use and risky sexual behaviours amongst WSW in Blantyre, Malawi. This was a cross-sectional study using quantitative method. Snowball sampling technique was used to recruit study participants. Participants were recruited through the Center for the Development of People (CEDEP), a Non-Governmental Organization working with sexual minorities in Malawi. 42 WSW aged 18-49 were recruited. A structured questionnaire was administered which focused on (a) demographic characteristics, (b) exploring self-reported HIV and STI prevalence and (c) drug usage and WSW sexual practices. 42 participants were recruited with a median age of 23 years (range 18-33). Self- reported HIV prevalence was 2% (1/42). Prevalence for Candida albicans infection was 29% (12/42) and genital warts 7% (3/42). One participant (2%) self-reported having syphilis in the past one year and had no history of sexual contact with men. Sexual practices in the past one year were also accessed. All study participants (100%) reported to have engaged in fingering and clitoris to clitoris sexual contact; (59%) had multiple female sex partners and (26%) were involved in female-male sex. (36%) reported using unsterilized sex toys and (28.5%) were involved in oral sex. Drug use in the past one year was also assessed. No participants reported injected drug use. However non-injectable drugs like Marijuana (50%), Cuba (7.14%) and Cocaine (12%) were reported. This was the first robust study on WSW in Malawi. It has demonstrated a low prevalence of self-reported HIV infection in WSW. However, STIs reported suggest that WSW are vulnerable to blood borne infections (syphilis). Episodes of warts and syphilis in a woman who had no history of sex with men suggest that female-female sex can transmit STIs.